2008
DOI: 10.1177/0148607108316187
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Exposure From Pediatric Parenteral Nutrition: Meeting the New FDA Regulation

Abstract: Currently available parenteral products used to make PN solutions contain amounts of aluminum that make it impossible to meet the new FDA rule of <5 mug/kg/d of aluminum exposure. Manufacturers must identify, develop, and adopt new methods to reduce the aluminum contamination in their products. Health care professionals should calculate aluminum loads in patients and make informed decisions when choosing PN products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 15 publications
2
48
0
Order By: Relevance
“…In practice, despite greater recognition of aluminum toxicity, little progress has been made on reducing exposure. Poole 3 recently concluded that meeting current FDA recommendations to limit aluminum exposure to <5mcg/kg/day is impossible in patients weighing <50kg using currently available PN products; and calculated aluminum exposure in infants <3kg was 30.3-59.9mcg/kg/day -indeed, somewhat higher than the calculated exposure of infants receiving standard PN solution in our trial.…”
Section: Discussionmentioning
confidence: 48%
“…In practice, despite greater recognition of aluminum toxicity, little progress has been made on reducing exposure. Poole 3 recently concluded that meeting current FDA recommendations to limit aluminum exposure to <5mcg/kg/day is impossible in patients weighing <50kg using currently available PN products; and calculated aluminum exposure in infants <3kg was 30.3-59.9mcg/kg/day -indeed, somewhat higher than the calculated exposure of infants receiving standard PN solution in our trial.…”
Section: Discussionmentioning
confidence: 48%
“…Regular PN piglets received PN with an aluminum contamination of 38 μg kg −1 d −1 . This is within the range of contamination levels seen in infant PN therapy used in clinical practice [3][4][5][6][7].…”
Section: Methodssupporting
confidence: 53%
“…Calcium may be provided in the form of calcium gluconate, calcium chloride, or calcium glycerophosphate. Due to aluminum contamination, calcium gluconate is now being progressively faced out by the industry to meet the rule of < 5 µg/kg/day of aluminum exposure in infants but it still remains frequently used in homemade hospital pharmacy preparations [95,96]. Calcium chloride is easy to use but its high chloride content needs to be considered in the electrolytes balance of the PN solution.…”
Section: Minerals Sourcesmentioning
confidence: 99%